Essays on political economy and development - (:unkn) unknown (My University, 2020)
This thesis is a collection of three essays in the fields of political economy and development. The first chapter explores the impact of early colonial leaders in French West Africa on the persistence of conflicts within countries and evaluates the link between the personality of colonial administrators and hostility towards the state. This chapter shows that the first administrators posted in colonial districts had a lasting effect on political conflicts. The second chapter explores the links between distance to capital cities, democratic institutions and access to health services in Sub-Saharan Africa. I show that distance to capital cities has a negative effect on access to basic maternal and child health services in less democratic sates, but not in more democratic ones. Investigating the role of political representation, I find that in the absence of strong democratic institutions increasing the political representation of women is also associated with a more equal spatial distribution of health services. The third chapter looks at informal market mechanisms in the health sector and evaluates of the prevalence of informal payments in inpatient public health facilities in Viet Nam. I observe that informal payments were negatively correlated with public health expenditures and practitioner incomes and positively correlated with beds per physicians. Examining impacts on the quality of health care received, results suggest that the quality of health services did not respond to informal payments but rather that patients were more likely to make informal payments when the supply of public health services was more limited.
Keywords: African Research